G.F. Dormidontov's report on A.A. Simolin's doctoral dissertation 'Influence of the Moment of Gratuitousness in Civil Law' - K.M. Arslanov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The year 2016 marks 100 years since Aleksandr Aleksandrovich Simolin (1879–1920), the last prerevolutionary head of the Department of Civil Law and Civil Procedure of Kazan University, defended his doctoral dissertation “Influence of the Moment of Gratuitousness in Civil Law”. In the last issue of “Uchenye Zapiski Kazanskogo Universiteta. Seriya Gumanitarnye Nauki” (Arslanov K.M. “Influence of the Moment of Gratuitousness in Civil Law”: 100 years since doctoral dissertation defense by A.A. Simolin. Uchenye Zapiski Kazanskogo Universiteta. Seriya Gumanitarnye Nauki, 2016, vol. 158, no. 2, pp. 311–321. (In Russian)), the procedure of defense of the dissertation by A.A. Simolin on October 23, 1916 and its main ideas were considered. This paper aims at analysis of G.F. Dormidontov's report on A.A. Simolin's dissertation. G.F. Dormidontov (1862–1919) was the graduate (1876), lecturer (1876–1917), and rector of Kazan University (1909–1917). He is known as the outstanding representative of the Russian prerevolutionary civil law science, Kazan juridical school in particular. This is the first time when the report, which is currently stored in the National Archives of the Republic of Tatarstan (Russia), has been reproduced verbatim. The important manuscript has been introduced into the scientific discourse, thereby providing the general public with an opportunity to learn the views of the famous predecessor.